CONVENTIONAL AND NONCONVENTIONAL FISHING TECHNIQUES USED BY RURAL FOLK IN MANDAL VALLEY, PAURI GARHWAL, UTTARAKHAND - BAHUGUNA, PANKAJ; JOSHI, HEMANT K.; DOBRIYAL, ANOOP K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
MandaI is an important river of Garhwal Himalaya, which ad.coIourfuI fišh fauna. The rural folk are dependwit on this river for protein rich animal diet. The paper describes some fishing and overfishing methods commonly LJ by the folk.